Adolescent Sibling Associations among Alcohol, Cannabis, and Sexual Risk Behavior: A Test of Interdependence. (24th August 2022) - Thomas, Sarah A.; Micalizzi, Lauren; Meisel, Samuel N.; Price, Dayna; Spirito, Anthony
Abstract: Background: Although siblings are conceptualized as a salient social influence during adolescence, few studies have examined how adolescent siblings influence each other's substance use and risky sexual behavior. Objectives: In this study, we investigated the influence of alcohol use days, cannabis use days, and cannabis and alcohol co-use days on the sexual risk behavior of siblings while accounting for dyadic influence. Methods: At the baseline visit for a randomized controlled trial for adolescents referred due to parents' concerns about their substance use ("referred adolescents"; n = 99; Mage =15.95; 38.38% female), we assessed alcohol and cannabis use days as well as sexual risk behavior of the referred adolescents and their sibling (Mage =15.03; 51.52% female). We computed the number of days in the 30 days prior to the baseline that alcohol and cannabis use occurred on the same day. Using a cross-sectional actor partner interdependence model, we tested two models of how adolescents' substance use is associated with their own ("actor effect") and their siblings' ("partner effect") sexual risk behavior—one model for alcohol and cannabis use, and one model for daily co-use. Results: For referred adolescents and their siblings, within an individual, greater alcohol, cannabis, and daily co-use was significantly associated with sexual risk behavior (actor effects). Furthermore, more sibling co-use days was positively associated with referred adolescent sexual risk behavior (partner effect), representing interdependence. Conclusion: These findings confirm the influence siblings have on one another's risky behavior in adolescence and have implications for prevention and intervention efforts for adolescent substance use.